Customers Perception Effect on Purchase Decision on Soccer Jersey (Case: ADIDAS Jersey) - Adythia, Stephanus; Hudrasyah, Herry (Journal of Business and Management, 2015)
Abstract.Soccer jersey development throughout past two decades is influenced by technology and sport fashion design. Soccer jersey business becomes a multi-million dollars business which circulates all over the world because themain market for soccer jersey is the soccer fans itself. For soccer jersey business, Indonesia is one of the its biggest market, especially in the Asia Pacific Region, Indonesia reached this status because of Indonesians craziness for soccer as proven by the enthusiasm to international soccer matches. Soccer jersey for international teams like Manchester United, Chelsea, Real Madrid, etc. is easily found but questions arise when it comes to the reasons behind why people in Indonesia is willing to spend their money on soccer jerseys and how Indonesians perceive this soccer jersey business.  This research’s purpose is to find if there are any influences on customer perception to purchase intention for soccer jersey products.230 people are taken as random samples to see their opinion about the brand, physical factor, image perception, and past experience influence people if they want to buy a soccer jersey. Interestingly, the result is there are no significance influence from those 4 factors to customers’ purchase intention for soccer jersey but the influence comes from the customers’ favorite soccer team.Keywords: Jersey, Purchase Intention, Customer Perception